Programmer's guide to the EGA, VGA and Super VGA Cards (Includes graphics accelerators!) - Richard F Ferraro (Addison-Wesley, 1994)
This book gives theknowledge and skills for successful graphics programming. It explains the PC graphics environments and graphics programming principles, and details the features and operation of the Super VGA, VGA, XGA, 8514/A, and EGA graphics standars